Implementation of Lesson Study Based Accounting Learning with Student Facilitator and Explaining Learning Model - Ijah Mulyani Sihotang; Pipit Putri Hariani MD (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to analyze lesson study-based accounting learning with Student facilitator and Explaining learning models and to describe how student accounting learning outcomes were implemented by implementing lesson study-based accounting learning with Student Facilitator and Explaining learning models. The background of this research is motivated by the low ability of students to understand accounting, this is because a small proportion of accounting students have a background from high school social studies or SMK BM Accounting so that a small proportion of students know accounting, let alone understand it and result in low accounting learning outcomes. The object of this research is the accounting students of Semester II FKIP UMSU in the 2019-2020 Academic Year. This research is descriptive, total population of 32 people. Research instruments were tests and observations. The research procedure is by applying the learning model Student facilitator and Explaining based on lesson study. The data analysis technique used is descriptive analysis technique. The results showed that the results of learning accounting were still in the high category with an average count of 77.4. If the value ranges were made into category B, the results of observations related to student learning activities were in the inadequate category because most of the students had maxed out. In learning activities in class.